An Assessment of Total Quality Management: A Comparative Study between Restaurants of Five Stars’ Hotels and Classified Restaurants in Jordan - أبو دلو، فوزات أسامة; العودات، أريج شبيب (إربد, 2020)
This research explores the implementation of total quality management (TQM) in restaurants of five stars' hotels and classified restaurants in Jordan. A hybrid research methodology, including quantitative and qualitative approaches to gather and analyze the data was used, the perceptions on the implementation of TQM in five stars, hotel restaurants and classified restaurants were explored from different points of views including employees, managers, and customers. Their views were investigated through two stages. The qualitative stage revealed the perceptions and awareness of employees on TQM, therefore, to assess the implementation of TQM practices. The respondents were asked about main issues of TQM including: employees' involvement and empowerment, communication, and customer focus. As for quantitative stage, a questionnaire was distributed to customers in restaurants and hotels, to survey the following dimensions: physical supplies, physical facilities, equipment, staff, complain response action, and food menu. The findings showed that classified restaurants and five-star hotels in Jordan do not apply all principles of total quality management, but rather focus on few of them (e.g. focus on customer), and they still rely on traditional management totally rather than applying the TQM practices.
Keywords: النشاط السياحي -- الجودة الشاملة -- السياحة الأردنية -- الفنادق السياحية -- الأردن